2019
DOI: 10.1111/apt.15248
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial response to mycophenolate mofetil by patients with autoimmune hepatitis who have failed standard therapy, is predicted by older age and lower immunoglobulin G and INR levels

Abstract: Summary Background Mycophenolate mofetil is a commonly used salvage therapy for patients with autoimmune hepatitis (AIH). Aim To evaluate the predictors of response to mycophenolate rescue therapy to facilitate clinical decision making. Methods We performed a retrospective observational cohort study of AIH patients managed in 17 major Australian liver centres who received mycophenolate after an inadequate response or intolerance to corticosteroids with/without thiopurine(s). Baseline demographic, clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
(70 reference statements)
3
21
0
Order By: Relevance
“…We express our appreciation to Dr Fan et al for their interesting observations and questions relating to our study of mycophenolate mofetil (MMF) as a second-line therapy in autoimmune hepatitis that was refractory or intolerant of standard therapy. 1,2 We agree that our paper raises the question of how best to manage elderly patients (≥60 years), and whether MMF is safe and effective in this group. The data in our paper indicated that those with age >53 years had a significantly increased response to MMF: OR 25.3 (95% CI, 2.0-318).…”
Section: Editorsmentioning
confidence: 67%
“…We express our appreciation to Dr Fan et al for their interesting observations and questions relating to our study of mycophenolate mofetil (MMF) as a second-line therapy in autoimmune hepatitis that was refractory or intolerant of standard therapy. 1,2 We agree that our paper raises the question of how best to manage elderly patients (≥60 years), and whether MMF is safe and effective in this group. The data in our paper indicated that those with age >53 years had a significantly increased response to MMF: OR 25.3 (95% CI, 2.0-318).…”
Section: Editorsmentioning
confidence: 67%
“…Mycophenolate mofetil, a purine antagonist of different molecular structure and metabolism than the thiopurine drugs (Figure 1), 7,8,10 has been enlisted as a second‐line agent for azathioprine intolerance and nonresponse 187‐189,230 . MMF is hydrolysed by liver esterases to mycophenolic acid (MPA) which acts as a reversible inhibitor of IMPDH 7,8 .…”
Section: Overviewmentioning
confidence: 99%
“…1 We appreciate the novel and hard work of the authors. 1 We appreciate the novel and hard work of the authors.…”
mentioning
confidence: 96%
“…
EDITORS,We read with great interest the article by Nicoll et al evaluating the predictors of response to mycophenolate mofetil (MMF) rescue therapy in patients with autoimmune hepatitis (AIH). 1 We appreciate the novel and hard work of the authors. This is the largest study to examine predictors of treatment response in AIH patients receiving MMF who have failed standard therapy.
…”
mentioning
confidence: 96%